PC.99 PINC UK (Probiotics in Neonatal Collaboration in UK). (9th June 2014) - Balain, M; Oddie, S; Banait, N; Embleton, N; Sesham, R; Clarke, P
Abstract : Background: Probiotics have been shown to reduce the risk for definite Necrotising enterocolitis (NEC) and all-cause mortality in very low birth weight babies without any significant adverse effects in > 5000 babies 1–3. Some neonatal units administer probiotics routinely to babies less than 1500g or 32 weeks gestation. Objective: PINC UK (Probiotics in Neonatal Collaboration in UK) aims to share experiences in the use of probiotics and evaluation of their results in UK neonatal units. Methods: Retrospective analysis of all babies eligible for probiotics and all babies who received probiotics at Bradford Neonatology, Norfolk and Norwich University Hospitals and Royal Victoria Infirmary Newcastle from September 2011 to December 2013, using data from "Badger" patient information system. Results: Probiotics were administered to >300 babies with gestation ranging from 23 weeks to term. The lowest birth weight was 438 grams. Probiotics were started on median day 6 of life. Staff and parental acceptance was high, with >85% eligible babies known to have received probiotics. There has not been any confirmed septicaemia associated with the probiotic organisms and total antibiotics usage has not increased. There have not been any significant problems in administration of probiotics and no adverse effects have been noted with the use of probiotics. Conclusion: Use of probiotics in preterm infants is a safe, low cost, evidence based intervention. We have seen no evidence of probiotic septicaemia. Systematic reviews suggest benefits may accrue to babies receiving them. We hope our experience of administration, and auditing usage will help other units. References: Alfaleh K, Anabrees J, Bassler D, Al-Kharfi T. Probiotics for prevention of necrotizing enterocolitis in preterm infants. Cochrane Database Syst Rev . 2011; Mar 16(3) Deshpande G, Rao S, Patole S and Bulsara M. Updated meta-analysis of probiotics for preventing necrotizing enterocolitis in preterm neonates. Pediatrics 2010;125:921 Mihatsch WA, Braeggerb CB, Decsic T, Kolacekd S, et al . Critical systematic review of the level of evidence for routine use of probiotics for reduction of mortality and prevention of necrotizing enterocolitis and sepsis in preterm infants. Clinical Nutrition 2012;31:6e15